Color as temporary tool of urban regeneration - Cristina Boeri; Daniela Calabi; Mario Bisson (Agathón)
The contribution presents the reference framework and the first results of a research aimed at exploring and experimenting intervention strategies and solutions that address the issue of urban regeneration of critical places within the city, enhancing the possibilities to intervene easily, quickly and temporarily through color in a relationship of dialogue with the specificities of the territory and the local identities. Color, a design component transitory by nature and linked to the ‘superficial’ aspects of the existing, presents itself as a privileged tool of intervention, generating results of great visual impact at relatively sustainable costs, in a sensitive and dynamic process of adaptation to the rapid needs that characterize the contemporaneity.